MINAT BELAJAR SISWA TERHADAP PEMBELAJARAN PJOK DENGAN PERMAINAN “CONE DRIBLLE RACE” SISWA KELAS III - Gustanul Arik; Setiawan Irwan; Sagitarius Andri Prasetyo (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to evaluate the increase in students' learning motivation in PJOK subjects through the implementation of the Cone Dribble Race game. The study used a descriptive quantitative approach with a pre-test and post-test design. The subjects of the study were 30 students of grade III SDN Jagalan 1, Kediri City. The research instrument was a Likert scale questionnaire and the data were analyzed using descriptive statistics. The results showed a significant increase in students' learning motivation after the game was implemented, with an average score increasing from 32.71 in the pre-test to 38.64 in the post-test. These findings imply that a game-based learning approach has the potential to be effective in increasing student participation and motivation in PJOK learning.